Response of Maise to Different Levels of Nitrogen - Ojha, BR (Journal of the Institute of Agriculture and Animal Science, 2006)
An experiment was conducted at the Institute of Agriculture and Animal Sciences, Rampur, Chitwan, Nepal during the summer season of 2003 to evaluate the response of Arun 2 variety of maize to different levels of nitrogen under field conditions. The experiment was conducted using Randomised Complete Block Design (RCBD) with three replications. Results showed a highly significant difference among treatments with respect to yield. Application of 90 kg N per ha gave the highest grain yield (5.46 ton/ha) and 150 kg/ ha gave the lowest yield (4.91t/ha). But the non-significant results were found with respect to plant height, cob height, days to 50 % silking, days to maturity and number of plants per plot among treatments. The mean values for number of plants per plot, plant height, cob height, days to 50 % silking after sowing, days to maturity after sowing and yield /ha were found 21.3, 192.3 cm, 94.3 cm, 50.3, 87.5 and 5.18, respectively, Strong correlation of 0.81 and 1 were found between the traits plant height and cob height and days to 50 % silking and days to maturity respectively. In contrast, negative correlation was found between the traits plant height and yield, and cob height and yield. Key words: Nitrogenous fertiliser, yield component, maize J. Inst. Agric. Anim. Sci. 27:149-152 (2006)